Interrelation of ophthalmic pathology with the condition of the musculoskeletal system of visually impaired schoolchildren - T. S. Egorova; T. S. Smirnova (Российский офтальмологический журнал)
Purpose: to study the state of the musculoskeletal system of visually impaired schoolchildren using a topographic system TODP and analyze the prevalence of spine conditions for different ophthalmic pathologies. Material and methods. 188 visually impaired high school students and 60 students with high visual acuity (the control group) were tested using computer optic topography COMOT and the TODP topographic system. Results. The most significant conditions of the musculoskeletal system, including scoliosis, kyphosis, hyperlordosis, torsion, flatfoot, deformities of the lower extremities and the thorax were diagnosed in students with postsurgical aphakia (artiphakia) after congenital cataract extraction, with retinopathy of prematurity, and with high degenerative myopia. Pelvis tilt is most often observed in students with monocular vision. Conclusion. The need for an integrated approach to the rehabilitation of visually disabled children was confirmed. Regular orthopedic checkup of the musculoskeletal system of visually impaired children and adolescents is recommended. Preventive measures should be taken to avoid negative consequences of posture and spine deformations for internal organs and systems, which aggravate the disability // Russian ophthalmological journal. 2017; 10 (3): 13-21. doi: 10.21516/2072-0076-2017-10-3-13-21 (in Russian). For citations: Egorova T.S., Smirnova T.S. Interrelation of ophthalmic pathology with the condition of the musculoskeletal system of visually impaired schoolchildren. Russian ophthalmological journal. 2017; 10 (3): 13-21. doi: 10.21516/2072-0076-2017-10-3-13-21 (in Russian).